Punk Farm - Krosoczka, Jarrett (New York : Alfred A. Knopf : Distributed by Random House, 2005)
At the end of the day, while Farmer Joe gets ready for bed, his animals tune their instruments to perform in a big concert as a rock band called Punk Farm.
Keywords: Musicians -- Fiction; Rock music -- Fiction; Domestic animals -- Fiction; Farm life -- Fiction